Gulf Cooperation Council : How Can Growth-Friendlier Expenditure-Based Fiscal Adjustment be Achieved in the GCC?. (Policy Papers; Policy Paper ;, 2017)
growth in expenditure, GCC governments have started to implement significant fiscal consolidation measures, but more needs to be done. Rapid population growth and booming oil revenues led to large increases in government spending in the GCC in the decade to 2014, which now stands high by international standards. This expenditure is dominated by compensation of employees and other current spending which are large in percent of GDP compared to Emerging Market (EM) countries and other oil exporters. This keeps overall spending above levels consistent with long-term fiscal sustainability and intergenerational equity. The international experience with large fiscal adjustments provides some key lessons for GCC countries. This experience suggests that growth outcomes improve when fiscal adjustments are sustained as part of credible multi-year fiscal plans, rely on expenditure more than revenue adjustment, and lead to improvements in expenditure composition (away from current outlays to more productive spending) and the structure of revenue (away from direct to indirect taxation). Successful fiscal adjustments also tend to be part of wider structural reforms that support growth.